Broadband Signal Transmission Using Radio Over Fibre System - Yaakob, Syamsuri (2009)
This thesis explores broadband tranmission over the ROF system. A system is proposed, where directly modulated wireless local area network (WLAN) and externally modulated baseband (BB) signals, are simultaneously transmitted.